Aluminium stress examination of Pasaman local brown rice genotypes in early phase - Indra Dwipa (JERAMI : Indonesian Journal of Crop Science, 2019)
One of brown rice resistance is tolerant to Aluminium stress. The research was conducted in Seed Technology Laboratory and shade net house of Faculty of Agriculture, Andalas University form March to June 2017. The research aimed to study the tolerance of 6 Pasaman brown rice genotypes to Al stress. Factorial design in Completely Randomized Design was used in this research. The first factor was brown rice genotypes, Sigambiri,LadangTalamau, SikarojukSilomlomPulen and Perbatasan. The second factor was AlCl3 doses, 0 ppm, 5 ppm, 10 ppm, 15 ppm and 20 ppm. The data was analysed by F test and extended by Duncan’s New Multiple Range Test in 5%. The result showed that there was interaction between Al concentration and 6 brown rice genotypes for height of plant, length of leaves. Based on tolerance level, all genotypes were grouped to Moderate-Tolerant level.